2015
DOI: 10.1371/journal.ppat.1005154
|View full text |Cite
|
Sign up to set email alerts
|

Heterosexual Transmission of Subtype C HIV-1 Selects Consensus-Like Variants without Increased Replicative Capacity or Interferon-α Resistance

Abstract: Heterosexual transmission of HIV-1 is characterized by a genetic bottleneck that selects a single viral variant, the transmitted/founder (TF), during most transmission events. To assess viral characteristics influencing HIV-1 transmission, we sequenced 167 near full-length viral genomes and generated 40 infectious molecular clones (IMC) including TF variants and multiple non-transmitted (NT) HIV-1 subtype C variants from six linked heterosexual transmission pairs near the time of transmission. Consensus-like g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
147
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(160 citation statements)
references
References 52 publications
11
147
2
Order By: Relevance
“…The replicative capacity of viruses can influence their reproductive ratio (R 0 ) and thus their ability to expand an initial infection (51). Comparing IMCs from unrelated subjects, we previously failed to detect differences in the growth potential of TF and chronic HIV-1 strains (26), and similar results were reported for donor and recipient viruses from transmission pairs (27,28). Here, we compared the replicative capacity of limiting dilution-derived isolates in normal donor CD4 + T cells.…”
Section: Increased Env Content Is Not a Characteristic Feature Of Tramentioning
confidence: 55%
See 2 more Smart Citations
“…The replicative capacity of viruses can influence their reproductive ratio (R 0 ) and thus their ability to expand an initial infection (51). Comparing IMCs from unrelated subjects, we previously failed to detect differences in the growth potential of TF and chronic HIV-1 strains (26), and similar results were reported for donor and recipient viruses from transmission pairs (27,28). Here, we compared the replicative capacity of limiting dilution-derived isolates in normal donor CD4 + T cells.…”
Section: Increased Env Content Is Not a Characteristic Feature Of Tramentioning
confidence: 55%
“…We previously reported that TF viruses were 2-fold more infectious than chronic viruses from unrelated subjects (26), but two subsequent studies failed to identify virus infectivity as a determinant of transmission fitness (27,28). Here, we used TZM-bl cells, which express luciferase under the control of an HIV-1 promoter (48,49), to determine the per-particle infectivity of CD4 + T-cellderived viral stocks.…”
Section: Increased Env Content Is Not a Characteristic Feature Of Tramentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Deymier et al [4] did not observe selection for higher infectivity in a study of 6 transmission pairs, although this could be due to the use of DEAE-dextran in their infectivity assay and/or the presence of subclinical inflammation. The Figure 1.…”
Section: Discussionmentioning
confidence: 82%
“…This transmitted founder virus is rarely the dominant variant, suggesting that transmission is not entirely stochastic but favors certain viral phenotypes [3][4][5]. The most likely determinants of this bottleneck are the physical and immunological properties of the healthy genital mucosa, which constitutes an efficient barrier to HIV acquisition and is able to block most unprotected sexual exposures [6].…”
mentioning
confidence: 99%